Analisis Variasi Sudut Wedge pada Treatment Planning System Berdasarkan Dose Volume Histogram (DVH) pada Ca Mammae Sinistra - Nurjannah, Sri; Robert Janssen Stevenly; Kadek Subagiada; Erlinda Ratnasari Putri (Jurnal Inotera, 2024)
Breast cancer ranks first in terms of the highest number of cancers in Indonesia and is one of the first contributors to cancer deaths. According to IARC, radiotherapy is one of the most important modalities in the treatment of breast cancer. Radiotherapy is a type of treatment that uses ionizing radiation to kill cancer cells without damaging surrounding healthy tissue. To obtain an even or homogeneous dose distribution on an uneven skin surface, a wedge is used so that the radiation given to the tumor area is truly optimal and the surrounding healthy tissue receives a minimum dose. This research was carried out by evaluating the Planning Target Volume (PTV) value based on ICRU-83 and dose distribution in Organs at Risk (OAR) based on QUANTEC standards at four different wedge angles, namely 15°, 30°, 45°, and 60°, used the 3D-CRT technique of tangential radiation with a dose of 50 Gy in 25 fractions on 5 left-sided breast cancer patients. The research results showed that the average Homogeneity Index (HI) values for the 15°, 30°, 45° and 60° wedges were 0.286, 0.346, 0.436 and 0.578, respectively. In the left and right lung dose distribution, the results obtained for the 15°, 30°, 45°, and 60° wedge were respectively 2231.4 and 116.2 cGy, 2257.8 and 114.6 cGy, 2141 and 100 cGy, and 2059.4 and 88.8 cGy. For the average dose distribution to the heart, the values obtained at the 15°, 30°, 45°, and 60° wedges were 2005.6 cGy, 2040.4 cGy, 1930.6 cGy, and 1844.4 cGy, respectively. where the average dose received by OAR is still below the limit allowed by QUANTEC. Using a wedge angle of 15° provides a homogeneous dose distribution for the PTV and a wedge angle of 60° provides the lowest dose distribution for the OAR.